2021
DOI: 10.1186/s12886-021-02006-1
|View full text |Cite
|
Sign up to set email alerts
|

Macular perfusion density evaluation in constant and intermittent exotropia by means of optical coherence tomography angiography

Abstract: Background To quantify and compare retinal microvascular features using optical coherence tomography angiography (OCTA) in constant (XT) and intermittent exotropia (IXT). Methods An observational cross-sectional study was conducted from September 2020 to November 2020 at the Affiliated Eye Hospital of Wenzhou Medical University. OCTA examination was performed to evaluate the macular perfusion density of the deep capillary plexus (DCP), superficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…Compared with the control group, we found that in the exotropia group, SCP was greater in the temporal quadrant in the deviated eyes, and lower in the nasal quadrant in the dominant eyes in the outer macula. The previous reports were almost inconsistent [ 30 , 33 ]. Li-Ying L. et al [ 30 ] analyzed 29 constant strabismic patients and compared the macular microvasculature with age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, we found that in the exotropia group, SCP was greater in the temporal quadrant in the deviated eyes, and lower in the nasal quadrant in the dominant eyes in the outer macula. The previous reports were almost inconsistent [ 30 , 33 ]. Li-Ying L. et al [ 30 ] analyzed 29 constant strabismic patients and compared the macular microvasculature with age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the transient vascular changes occurred only in the SCP is unclear. Zhai et al [ 26 ] reported that macular perfusion densities of the SCP in 3 × 3-mm scans and DCP in 6 × 6 -mm scans were lower in the deviating eyes than in the fixating eyes of patients with exotropia, which may be related to the constant lack of normal visual information received by the deviating eye. Unlike Zhai’s study, there was a significant perfusion decrease only in the SCP in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The previous reports have been inconsistent. (23,25) Liying L. et al (23) analysed 56 constant strabismus patients and compared macular microvasculature with age-matched healthy controls. They indicated that no signi cant difference was found in RT, SCP, and DCP among dominant eyes, nondominant eyes, and control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated DCP vessel density, which was lower in all quadrants except the superior quadrant Some previous studies also showed similar results. Zhai J. et al (25) studied 40 exotropia patients using OCTA compared with 36 controls. The macular perfusion density of DCP in the nondominant eyes of constant exotropia and intermittent constant exotropia patients was signi cantly lower than that of the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation